The Design and Development of Online Course Materials: Some Features and Recommendations - Liliana Cuesta (Universidad Nacional de Colombia, 2010)
This article discusses various features in the design and implementation of online course materials. The author provides a critical review of some instructional design patterns and expands on the alignment among instruction, motivation and learners' performances as part of a curriculum design process. In this context, the author emphasizes the value of permanent analysis and assessment to support an efficient management of online environments in which knowledge construction and interaction find common ground on which to evolve. The author argues in favor of steady and competent efforts to implement varied educational strategies posed both for online instructors and learners. Practical recommendations are espoused for the designers of online courses.